The Analysis of Births and Household Poverty Levels with the Consideration of the Material Effect of the ‘Family 500 Plus’ Programme - Rajfur, Piotr; Rajfur, Joanna; Hys, Katarzyna (Journal of Public Governance, 2021)
Objectives: The objective of the article is to assess the performance of the Polish government’s family policy programme known as the ‘Family 500 Plus’ programme, with special consideration of the material effect. In this study, the authors attempt to assess the performance of the ‘ Family 500 Plus’ programme (Journal of Laws of 2016, item 195 as amended) in the first years of its operation, answering the question about whether the implementation of the government’s family policy programme has contributed to an increase in births and a decrease in the level of poverty in households in Poland. Research Design & Methods: The authors conducted research on the chosen indicators, using the method of incomplete induction based on inductivism and verificationism. The study relies on the literature review and desk research. The analysis made use of statistical data provided by the Central Statistical Office (GUS). In the preparation of this article, legal acts placed on the Website of the Sejm of the Republic of Poland – as well as relevant scientific publications – were used. Findings: Since the launch of the ‘Family 500 Plus’ programme, the number of births has clearly been gradually increasing. In the analysed period, we have laso observed positive birth changes within large families. The developmental trend of births showed an upward tendency in the first two years of the Act in force and changed in 2018. This clear change can be observed in the area of extreme poverty in households in 2015–2018. In households with at least two children up to the age of 18, there was a change in the extent of extreme poverty by almost 50%, which was approaching the extreme poverty line in a given year in Poland. Implications & Recommendations: In view of the changes in trends in the number of births observed since 2018 as well as the extent of extreme poverty in households, the authors recommend further observation and analysis of the indicators presented in this study. Contribution / Value Added: The presented analysis of the indicators and the observation of development trends will allow for a proper adjustment of family policy. In the future, this might make it easier for the public authorities to take appropriate decisions concerning family policy. Article classification: research article